Analysis of Class II Intermaxillary Elastics Applied Forces: An in-vitro Study - Castroflorio, Tommaso; Sedran, Ambra; Spadaro, Francesca; Rossini, Gabriele; Cugliari, Giovanni; Quinzi, Vincenzo; Deregibus, Andrea (Frontiers in Dental Medicine, 2022)
Objectives The aims of this study were: 1) to assess the average inter-arch distances characterizing Class II malocclusions, 2) to analyze the applied forces at those distances by different elastics and 3) to compare measured forces with those declared by manufacturers, both in dry and wet environments. Materials and methods Settings and Sample population: Class II models of 167 adult subjects (96 F and 71 M, age: 28 ±3) referred to the orthodontic department of the University of Turin, between January 2018 and January 2020, were collected. Distances between facial axes (FA) points of upper canines and lower first molars (A), upper first premolar and lower first molar (B), upper second premolar and lower first molar (C), upper canine and lower first premolar (D), upper canine and lower second premolar (E), were measured, using 3Shape Ortho® Viewer program. Different elastics’ diameters and forces were tested at those distances. MTS Insight® Electromechanical Testing Systems was used to measure elastics’ tensile forces. The applied force were measured in dry (T0) and wet conditions, after 1h (T1), 6h (T2) and 12h (T3). Results Average distances were calculated: A=24.64mm (SD 2.10), B=16.3mm (SD 1.94), C=9.78mm (SD 1.77), D=9.8mm(SD 1.88) and E=15.99mm (SD 2.06). Significant differences (p<0.05) were highlighted between the measured force and the force declared by manufacturers, and all elastics had a significant force decay (p<0.05). Conclusions 3/16" 4.5 oz are the most reliable elastics in terms of applied force with respect to the declared one and in terms of force degradation.